Planctomycetes-Verrucomicrobia-Chlamydiae Bacterial Superphylum: New Model Organisms for Evolutionary Cell Biology - Damien P. Devos (Frontiers Research Topics, 2017)
The Planctomycetes, Verrucomicrobia, Chlamydiae (PVC) and related phyla have recently emerged as fascinating subjects for research in evolutionary cell biology, ecology, biotechnology, evolution and human health. This interest is prompted by particular characteristics observed in the PVC superphylum that are otherwise rarely observed in bacteria but are however still poorly described or understood, such as the presence of a complex endomembrane system, or compacted DNA throughout most of the cell cycle. Therefore, the members of the PVC superphylum represent an excellent example of the value of studying bacteria other than 'classical' models.